Sympathetic ophthalmia following postoperative endophthalmitis and evisceration - Androudi, S (LITHOGRAPHIA Antoniadis I.-Psarras Th. G.P., 2010)
Purpose: To report a case of sympathetic ophthalmia (SO) following purulent postoperative endophthalmitis and final evisceration of the affected eye. Methods-Results: A 64-year-old male underwent phacoemulsification complicated by endophthalmitis. Five months latter the eye was painful and had no light perception so an evisceration was performed. Two weeks latter granulomatous posterior uveitis developed in the fellow eye. SO was diagnosed and the patient was started on prednisone and cyclosporine. The inflammation subsided and visual acuity improved to 20/30. Conclusions: Bacterial endophthalmitis cannot prevent the development of SO. Prompt diagnosis and management is the most important factor for visual prognosis.